Beauty Standardization of Millennial Circle Skin Care - A Zahid; Agustini Kala Ayu; Siti Mariyam (An-Nisa': Journal of Gender Studies, 2022)
This article aims to find the relationship between beauty products in various Indonesian companies and female consumers, because the discourse on product relations with consumers is attractive to the millennial generation. Until now, beauty products when the most in demand. Basic skincare needs have been consumed by the wider community, especially among teenagers, resulting in female beauty stigmatization as measured by an ideal body, beauty, white skin, and long-thin hair. This research is qualitative in nature with a literature study approach which is the basis for looking at the relationship between women from time to time. The results in various constructivism and discourses about the beauty of the female figure, Norman Fairclough's critical analysis method. While the data collected from books and articles as material, data analysis using data collection methods, data presentation, data reduction and concluding. The results showed that Millennials make skincare as a consumptive relationship to their bodies displayed in the image of a perfect woman. So that, the beauty legitimacy is measured by the beauty products they use as a symbol of themselves with constructivism.